Carbon sink dynamics and resilience thresholds of a volcanic island land–sea system in the Beibu Gulf: Evidence from CMIP6 simulations and sediment records since 1961 - Yitong Lin; Yuanfu Yue; Qunxin He; Qinyi Meng; Xiaoxiao Zou; Shixiong Yang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Growth-mode-independent glutamine/glutamate/aspartate metabolic shift and urea cycle remodeling driven by FOXA1 in benzo[a]pyrene-transformed human bronchial epithelial cells - Yujin Fu; Yanmin Qi; Yunkun Xing; Yitong Lin; Zhiyu Liu; Juanling Fu; Biyun Yao; Peng Zhao (Toxicology and Applied Pharmacology, 2026)

Corrigendum to ‘Machine Learning-Driven Recombinant Xylanase Synergized with Pediococcus pentosaceus: Directed Xylose-Lactate Conversion and Metabolic Mechanism of Lignocellulosic Waste’[Resources, Conservation & Recycling 234 (2026) Article 109058] - Jiajin Sun; Yujuan Zhang; Luyao Zhang; Chen Shen; Yitong Lin; Rong Zhao; Lei Chen; Qiang Liu; Cong Wang; Wenjie Huo; Gang Guo (Resources, Conservation and Recycling, 2026)

Machine learning-driven recombinant xylanase synergized with Pediococcus pentosaceus: directed xylose-lactate conversion and metabolic mechanism of lignocellulosic waste - Jiajin Sun; Yujuan Zhang; Luyao Zhang; Chen Shen; Yitong Lin; Rong Zhao; Lei Chen; Qiang Liu; Cong Wang; Wenjie Huo; Gang Guo (Resources, Conservation and Recycling, 2026)

Corrigendum to “Limonene-loaded nanostructured lipid carriers incorporated in hydrogels: Enhanced acid stability and controlled release properties” [Food Res. Int. 214 (2025) 116601] - Simin Feng; Yitong Tian; Jiahao Yu; Yang Lin; Alan Giovanini de Oliveira Sartori; Ping Shao (Food Research International, 2026)

Faecalibaculum rodentium- derived quinic acid- mediated Treg differentiation drives the attenuation intestinal inflammation by Agrimoniae Herba polysaccharides - Jiayan Hu; Yitong Yu; Zhibin Wang; Muyuan Wang; Yuxi Wang; Xiaowei Chen; Yuyue Liu; Mengyu Zheng; Chengtao Liang; Chenran Lv; Anqi Yang; Zhengdao Lin; et al. (Carbohydrate Polymers, 2026)

Tuning electron transfer and surface dual-sites for synergistic peroxymonosulfate activation toward efficient 2,4,6‑trichlorophenol degradation - Jingyi Wang; Yitong Liu; Wenhui Qiu; Lin Zhang; Kaige Li; Ran Wang; Bo Cao; Jianhua Qu; Ying Zhang (Process Safety and Environmental Protection, 2026)

Resource-efficient numerical computing and elastic wave behavior analysis in complex poroelastic media - Zhitao Zhang; Yuhang Guo; Zhuwen Wang; Baozhi Pan; Yibo Wang; Lin Gan; Wubing Wan; Zhaoqi Sun; Wenqiang Wang; Ruiyi Han; Jiaxu Guo; Yitong Cui (Computers and Geotechnics, 2026)

A graph-based C-BOM framework integrating multi-view xBOM data for efficient product carbon footprint assessment - Weitong Liu; Liming Wang; Fangyi Li; Lin Kong; Xingyuan Xiao; Yitong Wang; Yuqi Cui; Boyun Wang; Liuyuan Li (Journal of Cleaner Production, 2026)

Levan-derived oligosaccharides (LOS) prime barley against fungal pathogens through asparagine metabolism - Dan Lian; Yanjing Li; Jiaxin Ma; Junjie Zhou; Yitong Xia; Mengyuan Yang; Ruiming Lin; Huiquan Shen; Li Xu; Huijuan Zhang; Jingjing Xu; Wei Wu; et al. (Carbohydrate Polymers, 2026)

Excitation mechanisms and vibration response of a horizontal elbow in gas-liquid two-phase flow - Yitong Fu; Xiang Li; Bolun Ding; Yiran Duan; Lin Ding (Ocean Engineering, 2026)

Influence of Sea Surface Temperature on Precipitation Anomalies in Northeast China During the Late Summer, 2024: A Statistical Assessment Based on Generalised Equilibrium Feedback Analysis - Yitong Lin; Yihe Fang; Chunyu Zhao; Yu Zhang; Chang Liu; Xinze Li (International Journal of Climatology, 2026)
During the late summer (July–August) of 2024, the Northeast China (NEC) suffered extreme precipitation and severe floods, with rainfall in southern NEC marking the highest recorded since 1985. Using the daily precipitation records from 245 national meteorological stations across the NEC, this study analyses the characteristics of the rainfall anomalies and the associated large‐scale circulation patterns in the late summer of 2024. Based on the generalised equilibrium feedback analysis (GEFA) method, we investigate the response of precipitation and atmospheric circulation anomalies to sea surface temperature (SST) anomalies across various oceanic basins. The results indicate that the NEC precipitation anomalies in the late summer of 2024 exhibit a remarkable response to both the first empirical orthogonal function (EOF) mode of the North Pacific SST (NP1) and the second EOF mode of the tropical Atlantic SST (TA2). The NP1 features widespread positive SST anomalies extending from the Kuroshio Extension to the west coast of North America, and the TA2 is marked by positive anomalies in the northern tropical Atlantic and negative anomalies in the southeastern region. Both modes induce enhanced precipitation over NEC, with anomaly centres located southward, closely matching the observations. Specifically, the positive SST anomalies of the NP1 mode enhance the upward heat flux over the Japan Sea and its eastern regions, inducing positive geopotential height anomalies over Japan, thereby leading to an enhanced and northward anticyclone in the Northwest Pacific. Moreover, for the TA2 mode, the positive SST anomalies in the northern tropical Atlantic are closely associated with the downstream propagating Rossby wave train, resulting in an anomalous circulation pattern characterised by active Northeast China cold vortexes over the NEC and an intensified western Pacific subtropical high. These circulation anomalies facilitate the northward transport of warm and humid airflows to the NEC and promote the frequent convergence of cold and warm airflows over the NEC region, thereby contributing to the anomalously more precipitation over the NEC in the late summer of 2024. By quantifying the relative contributions of different SST modes, this study helps better target key precursors of NEC summer rainfall anomalies, which provides useful guidance for seasonal climate forecasting in NEC.

A geometric Cross-Propagation-Calibration method for SAR constellation based on the graph theory - Yitong Luo; Xiaolan Qiu; Bei Lin; Zekun Jiao; Wei Wang; Chibiao Ding (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Identification of multiple galectins as receptors for β-1,3-glucans - Xuejiao Xu; Zhen He; Yuanning Wang; Xiushi Jia; Andong Zhou; Yibing Wang; Yitong Li; Jieyi Long; Kevin H. Mayo; Lin Sun; Yifa Zhou; Zihan Zhao; et al. (Carbohydrate Polymers, 2026)

Symbiotic food grade fermentation enhances the multifunctional photoprotective activity of Tricholoma matsutake through metabolic remodeling - Yongyan Pei; Zhiqing Tang; Keyu Lin; Hongliang Li; Yitong Chen; Hua Cao (Food Bioscience, 2026)

Disparities in bioaccumulation of chlorinated organic pollutants in O. bartramii and seawater from the Northwest Pacific Ocean: Compound – specific mechanisms and health risks - Ci Wang; Xinran Liu; Yitong Gao; Zilan Wu; Li Zhang; Jingqian Xie; Xinyu Tian; Feng Wu; Xiaojie Dai; Bilin Liu; Tian Lin (Marine Pollution Bulletin, 2026)

Composite lemon/ginger essential oil emulsion based on pectin and sodium caseinate: Preparation, properties, and application in fresh-cut carrots preservation - Qin Chen; Bowen Li; Shuixian Huang; Yanbing Zhang; Lin Lu; Yitong Liu; Siyi Pan; Fengxia Liu (Food Chemistry, 2025)

New relationship and mechanisms between Northeast China Cold Vortex and pre-flood season precipitation in South China under global warming - Baihui Guo; Yihe Fang; Yitong Lin; Yiqiu Yu; Chunyu Zhao; Yu Zhang; Yamin Hu; Mingsheng Wang (Climate Dynamics, 2025)

A robust method for quantitative detection of β-1,3-glucan using Limulus polyphemus factor Gα fragment - Andong Zhou; Yitong Li; Yuanning Wang; Yibing Wang; Zhonghui Qiao; Kevin H. Mayo; Zihan Zhao; Lin Sun (Carbohydrate Polymers, 2025)

Limonene-loaded nanostructured lipid carriers incorporated in hydrogels: Enhanced acid stability and controlled release properties - Simin Feng; Yitong Tian; Jiahao Yu; Yang Lin; Alan Giovanini de Oliveira Sartori; Ping Shao (Food Research International, 2025)

Impact assessment of green finance reforms on renewable energy development - Yitong Zhu; Boqiang Lin; Runqing Zhu (Environmental Impact Assessment Review, 2025)

Liquid–liquid phase separation in normal hematopoiesis and hematological diseases - Lexuan Lin; Fang He; Xu Jin; Xiaoru Zhang; Yue Li; Di Wang; Jingwei Wang; Lingyue Zheng; Haoze Song; Xu Zhu; Qimei Cheng; Yitong Zhao; et al. (Cell and Tissue Research, 2025)

Unveiling high-light-use efficiency in Juglans mandshurica: Adaptive insights from leaf morphology and physiology - Qinhui Zhang; Dan Peng; Xiaona Pei; Yitong Chen; Zihan Yan; Mingrui Kang; Jinrong Hu; Yulu Pan; Jingxin Yu; Lu Xu; Huicong Lin; Xiyang Zhao (Forest Ecology and Management, 2025)

Tea tree oil Pickering emulsions stabilized by sodium lignosulfonate-zein covalent conjugate for fungicide delivery and enhanced control efficacy against peanut sclerotium blight - Jihao Zuo; Yitong Lin; Jiayuan Tian; Jinting Cai; Li Hao; Dongjie Liu; Qin Wang; Gengsheng Xiao; Xinhua Zhou; Hongjun Zhou (Chemical Engineering Journal, 2025)

Light regulates seed dormancy through FHY3-mediated activation of ACC OXIDASE 1 in Arabidopsis - Yitong Liu; Shuangrong Liu; Yanjun Jing; Jialong Li; Rongcheng Lin (Plant Molecular Biology, 2025)

Pectin based gels and their advanced application in food: From hydrogel to emulsion gel - Shuixian Huang; Yanbing Zhang; Qin Chen; Yitong Liu; Lin Lu; Muhammad Muntaqeem Arain; Zhaohui Li; Siyi Pan; Fengxia Liu (Food Hydrocolloids, 2025)

An integrated immunofluorescent detection system for automated and sensitive protein quantification based on a microfluidic flow cytometry platform - Lin Cheng; Yitong Li; Weiwei Ji; Jing Yan (Analytica Chimica Acta, 2025)

Space biological and human survival: Investigations into plants, animals, microorganisms and their components and bioregenerative life support systems - Lin Cheng; Yitong Li; Jing Yan (Life Sciences in Space Research, 2025)

Review of vibration induced by gas-liquid two-phase flow inside pipes - Lin Ding; Yitong Fu; Xiang Li; Jingyu Ran (Ocean Engineering, 2025)

The gratitude model of body appreciation and intuitive eating: Replication and extension of the model to explain intuitive eating facets among young adult women in China - Zizhen Huang; Siyu Wang; Yitong Lin; Tianxiang Cui; Wesley R. Barnhart; Christina M. Gaggiano; Feng Ji; Jinbo He (Appetite, 2024)

Long-term morphological evolution and restoration of dredged pits under sand mining in a funnel shaped Estuary - Liangwen Jia; Yitong Lin; Kanglin Chen (Ocean & Coastal Management, 2024)

Nature-based solutions still result in unfairness in carbon emissions - Yitong Yin; Gang Lin; Xiuhong Li; Rongjin Yang (Journal of Cleaner Production, 2024)

Characteristics and Mechanisms of Spring Tidal Mixing and Sediment Transport in a Microtidal Funnel-Shaped Estuary - Yitong Lin; Dezheng Liu; Mingen Liang; Tao Zhang; Enmao Huang; Zhiyuan Zhu; Liangwen Jia (Journal of Marine Science and Engineering, 2024)
Information about estuarine mixing and its control of sediment transport is crucial to elucidating the dynamics and evolution of estuaries. Here, the microtidal and funnel-shaped Zhenhai Estuary, located in the southwestern Pearl River Delta of China, is used to investigate the characteristics and mechanisms of water mixing and sediment transport based on observations from three spring tides. The results reveal that the studied estuary remains well mixed during spring tides from 2013–2022 despite its microtidal regime. Tidal stirring, which is enhanced by tidal energy convergence and benefits from the funnel-shaped geometry and shallow bathymetry, favors vertical mixing, contributing to the formation of strong mixing in the estuary. Due to the well-mixed regime, sediment transport in the estuary is dominated by the advective term, followed by a moderate tidal pumping term and minor estuarine circulation term. Accordingly, sediments within the estuary tend to be transported landward owing to the regulation of the funnel-shaped geometry, and a gradual but slow infilling trend is predictable. This paper deepens our understanding of hydrodynamics and sediment transport in microtidal estuaries.

Creating most needed customized bus services: A collaborative analysis of user-route dynamics - Chengcheng Yu; Haocheng Lin; Yitong Chen; Chao Yang; Ailing Yin; Quan Yuan (Transportation Research Part D: Transport and Environment, 2024)

Facile synthesis of polymer-derived K, Ti co-doped Li4SiO4-based sorbent for efficient and stable post-combustion CO2 capture - Liang Cai; Haifeng Xue; Xiuhong Yang; Yitong Lin; Xin Hu; Yingchun Zhang (Chemical Engineering Journal, 2024)

Impact of Anthropogenic Activities on Sedimentary Records in the Lingdingyang Estuary of the Pearl River Delta, China - Dezheng Liu; Yitong Lin; Tao Zhang; Enmao Huang; Zhiyuan Zhu; Liangwen Jia (Journal of Marine Science and Engineering, 2024)
High-intensity anthropogenic activities have greatly altered the estuarine-shelf depositional processes of sediments, and the intensity and frequency of the impacts of human interventions have far exceeded the natural development of estuarine systems. Since the reform and opening up, human activities such as dams, sand mining, channel dredging, and reclamation have already caused anomalous changes in the dynamical–sedimentary–geomorphological processes of the Lingdingyang Estuary (LE). Analyzing the impact of high-intensity anthropogenic activities on sedimentary processes and the hydrodynamic environment through sedimentary records can provide a scientific basis for predicting the evolution of the estuary and the sustainable development of the Guangdong–Hongkong–Macao Greater Bay Area. The aims of this study are to reveal the impact of varying intensity human activities across different periods on depositional pattern and conduct a preliminary investigation into the spatial differences in sedimentary characteristic attributed to human activities. Two cores (LD11 and LD13) located in the LE were selected for continuous scanning of high-resolution XRF, grain size, and 210Pbex dating tests, and scrutinized with the previous studies of the historical process of human activities in the LE. The results show the following: (1) The abrupt alterations in 210Pbex, geochemical indices, and grain size in LD13 happened in close proximity to the 95 cm layer, suggesting a shift in the sedimentary environment during 1994. (2) In the context of the continuous reduction in water and sediment flux into the LE after 1994, the large-scale and high-intensity human activities like sand mining, channel dredging, and reclamation are responsible for the sedimentation rate increase rather than decrease, the coarsening of sediment fractions, the frequent fluctuations in Zr/Rb, Zr/Al, Sr/Fe, and Sr/Al ratios, and the increase in anomalous extremes. (3) Sedimentary records found in locations varying in anthropogenic intensities differ greatly. Compared with the nearshore siltation area, the grain size composition in the channel area is noticeably coarser and exhibits a wider range of grain size variations. The 210Pbex is strongly perturbed and the vertical distribution is disturbed; the phenomenon of multiple inversions from the surface downwards is shown, making it impossible to carry out sedimentation rate and dating analysis, and the geochemical indicators have changed drastically without any obvious pattern. The evidence of the human activities can be retrieved in the sedimentary record of the estuary and provide a different angle to examine the impacts of the human activities.

Sub-Seasonal Predictability of the Northeast China Cold Vortex in BCC and ECMWF S2S Model Forecasts for 2006–2021 - Yiqiu Yu; Jie Wu; Yihe Fang; Chunyu Zhao; Zongjian Ke; Yitong Lin (Journal of Meteorological Research, 2024)

How do residents perceive ecosystem service benefits received from urban streets? A case study of Guangzhou, China - Chongxian Chen; Xiaoling Lin; Yitong Wu; Jiehang Xie; Jingyi Liu (Journal of Cleaner Production, 2024)

Biomaterials technology and policies in the building sector: a review - Lin Chen; Yubing Zhang; Zhonghao Chen; Yitong Dong; Yushan Jiang; Jianmin Hua; Yunfei Liu; Ahmed I. Osman; Mohamed Farghali; Lepeng Huang; David W. Rooney; Pow-Seng Yap (Environmental Chemistry Letters, 2024)
Traditional building materials have some drawbacks in the construction industry, particularly in terms of greenhouse gas emissions and energy consumption. Biomaterials derived from renewable sources are a promising alternative, significantly reducing the greenhouse effect and enhancing energy efficiency. However, traditional materials still dominate the construction sector, and there is a lack of understanding among some policymakers and developers regarding biomaterials. Here, we review building biomaterials and their policies and life cycle assessment through case studies. Bio-based materials have the potential to reduce over 320,000 tons of carbon dioxide emissions by 2050. They also exhibit advantages like decreasing water absorption by 40%, reducing energy consumption by 8.7%, enhancing acoustic absorption by 6.7%, and improving mechanical properties. We summarize recent advancements in mycelial materials, bioconcrete, natural fibers, and fiber-reinforced composites. We also explore the contributions of nanotechnology and microalgae technology in enhancing biomaterials' thermal insulation and eco-friendliness.

High resolution osteoclast-targeted imaging-guided osteoporosis alleviation via persistent luminescence nanocomposite - Xiao Lin; Kewen Zhang; Yang Li; Fang Nan; Jun Li; Hui Zhang; Wei Deng; Weihang Ding; Kaixuan Li; Nur Jarhen; Yitong Zhou; Xiao Yu; et al. (Chemical Engineering Journal, 2024)

Efficient carbon dioxide adsorption properties of cellular structure Li4SiO4 sorbents prepared by additive manufacturing based on polymer-derived ceramics strategy - Liang Cai; Guangfan Tan; Xiuhong Yang; Haifeng Xue; Yitong Lin; Xin Hu; Zhuoyuan Song; Yingchun Zhang (Chemical Engineering Journal, 2024)

Combined effects of massive reclamation and dredging on the variations in hydrodynamic and sediment transport in Lingdingyang Estuary, China - Kanglin Chen; Yitong Lin; Jing Liu; Zixiao He; Liangwen Jia (Frontiers of Earth Science, 2024)

Effect of phase change cooling vest on related thermal regulation factors in moderately hot environments - Bingbing Liu; Haiying Wang; Huxiang Lin; Yitong Su; Gang Wei; Zhewen Xu (Building and Environment, 2023)

Flood-driven jet flow and sedimentary regime in a river-dominated estuary - Jing Liu; Yitong Lin; Zixiao He; Feng Liu; Liangwen Jia; Wen Wei (Frontiers in Marine Science, 2023)
Sediment dynamics under floods are critical for estuarine morphological evolution. A two-dimensional coupled hydrodynamic/sediment transport numerical modeling was adapted to investigate the flood-driven jet structure and the resultant sedimentary regime in a river-dominated estuary, Modaomen Estuary, Pearl River Delta, China. The results show that the flow velocity of flood jet exhibits a Gaussian distribution in the transverse direction and shows a linear decreasing trend in the longitudinal direction. Moreover, a distinct zonation, including a zone of flow establishment (ZOFE) and a zone of established flow (ZOEF), was detected. The ZOFE was the core area of high turbidity and strong erosion and provided sufficient sediments to the ZOEF, where sediment diffused and settled. Due to the settling lag, the sediment diffusion and deposition areas were larger than those of the jet. Estuarine geomorphology regulates the shape of flood jet, which shows an asymmetry configuration with the main body located at the west side of the bifurcated estuary. Tidal dynamics play a crucial role in altering the range of jet diffusion, especially in the longitudinal direction. Increased flood intensity has little effect on the jet structure and erosion/deposition pattern, but significantly increases the magnitude of seaward current velocities and bed level changes, as well as the transverse diffusion range of jet and sedimentation.

Effects of organic substrates on sulfate-reducing microcosms treating acid mine drainage: Performance dynamics and microbial community comparison - Guodong Chai; Dongqi Wang; Yitong Zhang; Hui Wang; Jiake Li; Xiaosheng Jing; Haiyu Meng; Zhe Wang; Yuan Guo; Chunbo Jiang; Huaien Li; Yishan Lin (Journal of Environmental Management, 2023)

Expired yogurt-derived, three-dimensional water evaporator with sustainable self-cleaning and high mechanical properties for the desalination and purification of oil-contaminated seawater - Yahui Liu; Yitong Cui; Chunyu Yang; Huiming Lin; Feng Zhang; Kai Yu; Wei Guo; Fengyu Qu (Desalination, 2023)

Typhoon-induced suspended sediment dynamics in the mouth-bar region of a river/wave-dominated estuary - Mingen Liang; Jing Liu; Yitong Lin; Zixiao He; Wen Wei; Liangwen Jia (Marine Geology, 2023)

Screening of microalgae species and evaluation of algal-lipid stimulation strategies for biodiesel production - Yanan Yang; Shuhan Ge; Yitong Pan; Weiyi Qian; Shengnan Wang; Jian Zhang; Lin-Lan Zhuang (Science of The Total Environment, 2023)

A carbon-neutral scenario simulation of an urban land–energy–water coupling system: A case study of Shenzhen, China - Gang Lin; Dong Jiang; Yitong Yin; Jingying Fu (Journal of Cleaner Production, 2023)

The Coordinated Influence of Indian Ocean Sea Surface Temperature and Arctic Sea Ice on Anomalous Northeast China Cold Vortex Activities with Different Paths during Late Summer - Yitong Lin; Yihe Fang; Chunyu Zhao; Zhiqiang Gong; Siqi Yang; Yiqiu Yu (Advances in Atmospheric Sciences, 2023)

Two types of cold waves affecting northeast China and the corresponding different key regions of precedent sea ice and sea surface temperature - Yihe Fang; Yitong Lin; Chunyu Zhao; Shiqi Xu; Yi Lin; Yiqiu Yu (International Journal of Climatology, 2022)
Based on the daily minimum temperature data from 199 meteorological stations in northeast China (NEC), the cold wave (CW) processes in winter from 1980 to 2020 are identified. Then, by using the reanalysis 500‐hPa geopotential height data provided by the European Centre for Medium‐Range Weather Forecasts (ECMWF), the CWs are objectively classified into two types (abbreviated as Type 1 and Type 2) according to the corresponding atmospheric circulation through the hierarchical cluster algorithm (HCA). The relationships of the CWs with the Arctic sea sic (SIC) and sea surface temperature (SST) are revealed. For Type 1, the SIC in the north of the Barents Sea–Kara Sea is relatively less in the previous autumn, and a wave train propagating from the polar regions to Northeast Asia is stimulated under the ice–atmosphere interaction. This wave train further cooperates with the positive SST anomaly in the southern Indian Ocean to excite the low‐vortex circulation under the negative phase of Arctic Oscillation (AO) in winter, which is conducive to the occurrence of Type 1. However, the relatively low SST in the western Pacific warm pool in previous autumn stimulates a northward propagating wave train along the meridian, which increases the degree of meridionality of the atmospheric circulation over East Asia and thus indirectly causes the polar‐vortex‐splitting circulation under the positive AO phase, which favours the formation of Type 2. The numerical simulations can well reproduce the observational facts, further confirming the possible impact of the SIC and SST in the previous autumn on the two types of CW over the NEC.

Short-term variations and influencing factors of suspended sediment concentrations at the Heisha Beach, Guangdong, China - Jintang Ou; Haoyan Dong; Liangwen Jia; Xiangxin Luo; Zixiao He; Kanglin Chen; Jing Liu; Yitong Lin; Mingdong Yu; Mingen Liang (Acta Oceanologica Sinica, 2022)

Selenium Deficiency Leads to Changes in Renal Fibrosis Marker Proteins and Wnt/β-Catenin Signaling Pathway Components - Tingting Lin; Jiaqi Tao; Ying Chen; Yitong Zhang; Fenglan Li; Yutong Zhang; Xueqing Han; Zihui Zhao; Guiyan Liu; Hui Li (Biological Trace Element Research, 2022)

Histone deacetylase 6-mediated downregulation of TMEM100 expedites the development and progression of non-small cell lung cancer - Yanyun Wang; Minwen Ha; Man Li; Lin Zhang; Yitong Chen (Human Cell, 2022)

Classification of Northeast China Cold Vortex Activity Paths in Early Summer Based on K-means Clustering and Their Climate Impact - Yihe Fang; Haishan Chen; Yi Lin; Chunyu Zhao; Yitong Lin; Fang Zhou (Advances in Atmospheric Sciences, 2021)

Selenium Deficiency-Induced Damage and Altered Expression of Mitochondrial Biogenesis Markers in the Kidneys of Mice - Hehuan Lai; Tingting Nie; Yitong Zhang; Ying Chen; Jiaqi Tao; Tingting Lin; Tangdong Ge; Fenglan Li; Hui Li (Biological Trace Element Research, 2021)

Assessment of the Capability of ENSEMBLES Hindcasts in Predicting Spring Climate in China - Yitong Lin; Haiming Xu; Jing Ma; Haijun Li (Journal of Meteorological Research, 2019)